Citizenship and COVID-19: Syndemic Effects. Issue 8 (December 2021) - Shaw, Jo
Abstract: This article begins the task of outlining the impacts of the COVID-19 pandemic in relation to matters of citizenship, using what is termed a "syndemic analysis." This type of analysis places both the pandemic and citizenship in their wider contexts. The synergistic or intersectional thinking encouraged by the characterization of the pandemic as a syndemic, which links together health, socio-economic issues, and political questions, is useful for highlighting how much more vulnerable to many of the negative impacts of the pandemic in the sphere of citizenship are those who are also more vulnerable both to catching and suffering more seriously from the virus and to experiencing negatively the externalities of the measures taken to restrict social contact by shutting down economies. While the scope of the review is relatively broad and encompasses many different domains of "pandemic life, " what emerges from the analysis are important insights into how many of the impacts of the pandemic in fact operate at the intersection of citizenship and constitutional law and thus play out in the form of changes in relation to constitutional citizenship, both as ideal and as practice. The article takes an important step towards developing the use of constitutional citizenship as a framing device for understanding citizenship as putative full membership in a given society.